Experimental Research on the Sensitivity of PLC to Voltage Sag and Short Interruption - WU Yapen; XU Yonghai; LI Chenyi; WEI Pengfei (Kongzhi Yu Xinxi Jishu)
Using Chroma 61860 as the voltage sag generator, a popular PLC in the current market was selected to experimental research. Based on the experimental data, it achieved the tolerance curve of PLC to voltage sag and analyzed the influence on the point-on-wave of sag initiation to the the sensitivity of PLC. Meanwhile, it proposed improving suggestions for PLC manufacturers.